Microsatellites based Parental Polymorphism Survey in Elite Restorer Lines of Rice for Stacking Wide-compatibility Trait - Nanda, Kalpataru; Verma, Ramlakhan; Rout, Diptibala; Jena, Debarchana; Chakraborty, Nihar Ranjan (International Journal of Bio-resource and Stress Management, 2025)
A study was undertaken during kharif (June, 2021–November, 2021) at ICAR–Central Rice Research Institute (CRRI), Cuttack, Odisha, India to identify polymorphic simple sequence repeat (SSR) markers between the parental lines of two rice crosses: Cross-I (CR 22-153-1×Lemont) and Cross-II (CR 22-153-1×CR 22-1-5-1). The primary goal was to screen for parental polymorphisms that could facilitate marker-assisted background selection (MABS) to expedite the recovery of the recurrent parent genome (CR 22-153-1) in a marker-assisted backcross breeding (MABB) program aimed at introgressing the wide compatibility gene ‘S5n’ into the elite restorer line CR 22-153-1. A total of 320 hypervariable SSR markers, uniformly distributed across all 12 rice chromosomes, were employed for the polymorphism survey. Among these, 96 markers (30%) were polymorphic between CR 22-153-1 and Lemont, while 89 markers (27.81%) showed polymorphism between CR 22-153-1 and CR 22-1-5-1. The extent of polymorphism observed between CR 22-153-1 and Lemont ranged from 20.7% to 48.2% across the twelve chromosomes, while that between CR 22-153-1 and CR 22-1-5-1 ranged from 20.7% to 41.4%. These identified polymorphic SSR markers provided a valuable resource for precise background selection in backcross and near-isogenic line (NIL) populations in both the crosses. Their use enabled the effective introgression of the ‘S5n’ gene while minimizing linkage drag, thereby facilitating the development of wide-compatible, high-yielding restorer lines.